A lightweight vibro-acoustic metamaterial demonstrator: Numerical and experimental investigation. (March 2016) - Claeys, C.; Deckers, E.; Pluymers, B.; Desmet, W.
Abstract: In recent years metamaterials gained a lot of attention due to their superior noise and vibration insulation properties, be it at least in some targeted and tuneable frequency ranges, referred to as stopbands. These are frequency zones for which free wave propagation is prevented throughout the metamaterial, resulting in frequency zones of pronounced wave attenuation. Metamaterials are achieved due to addition of an, often periodic, grid of resonant structures to a host material or structure. The interaction between resonant inclusions and host structure can lead to a performance which is superior to the ones of any of the constituent materials. A key element in this concept is that waves can be affected by incorporating structural resonant elements of sub-wavelength sizes, i.e. features that are actually smaller than the wavelength of the waves to be affected. This paves the way towards compact and light vibro-acoustic solutions in the lower frequency ranges. This paper discusses the numerical design and experimental validation of acoustic insulation based on the concept of metamaterials: a hollow core periodic sandwich structure with added local resonant structures. In order to investigate the sensitivity to specific parameters in the metamaterial design and the robustness of the design, a set of variations on the nominal design are investigated. The stop bands are numerically predicted through unit cell modelling after which a full vibro-acoustic finite element model is applied to predict the insertion loss of the demonstrator. The results of these analyses are compared with measurements; both indicate that this metamaterials concept can be applied to combine light weight, compact volume and good acoustic behaviour. Abstract : Highlights: Design and analysis of resonant metamaterials for acoustic insulation. Numerical simulation of and experimental validation on a set of enclosures. Increased insertion loss through resonant inclusion in hollow core sandwich structure.